Advances in Mechanism Research on Polygonatum in Prevention and Treatment of Diabetes - Liu, Shuang; Jia, Qiao-Jun; Peng, Yi-Qing; Feng, Ting-Hui; Hu, Shu-Ting; Dong, Juan-e; Liang, Zong-Suo (Frontiers in Pharmacology, 2022)
Diabetes mellitus is a fast-growing disease with a major influence on people's quality of life. Oral hypoglycemic drugs and insulin are currently the main effective drugs in the treatment of diabetes, whereas chronic consumption of these drugs have certain side effects. Polysaccharides, saponins, flavonoids and phenols are the primary secondary metabolites isolated from the rhizomes of Polygonatum sibiricum Redouté [Asparagaceae], Polygonatum kingianum Collett & Hemsl [Asparagaceae] or Polygonatum cyrtonema Hua [Asparagaceae], which have attracted much more attention owing to their unique therapeutic role in the treatment and prevention of diabetes. However, the research on the mechanism of three Polygonatum is relatively scattered in diabetes. This review provides a summary of the research progress of three Polygonatum on diabetes and its complications, and revealed the potential anti-diabetic mechanism of three Polygonatum, and discussed the effect of different processed products of three Polygonatum in treating diabetes, for sake of thorough understanding its effects on prevention and treatment of diabetes and diabetes complications.